Digital Agricultural Technology for Smallholder Farmers: Barriers and Opportunities in Indonesia - Satria, Dias; Maghraby, Wahida; Setyanti, Axellina Muara (SOCA: Jurnal Sosial Ekonomi Pertanian, 2025)
The adoption of Digital Agricultural Technology (AgTech) has been widely promoted as a solution to enhance productivity, efficiency, and sustainability in Indonesia’s agricultural sector. However, in regions dominated by smallholder farmers, such as West Java, Central Java, Yogyakarta, East Java, Bali, and Lampung, AgTech uptake remains limited due to infrastructural, economic, and institutional challenges. This study aims to explore the barriers and opportunities in AgTech adoption among smallholder farmers, cooperatives, and agritech stakeholders. Utilizing a qualitative research approach, data were collected through in-depth interviews and focus group discussions involving 85 participants from diverse agricultural settings. Thematic analysis and NVivo-assisted sentiment mapping were used to analyze stakeholder perspectives. Results reveal that AgTech adoption is progressing but uneven, with persistent challenges including limited digital literacy, unreliable internet and electricity, dependence on middlemen, and misalignment between infrastructure investment and training. Successful public-private partnerships (PPPs) and targeted training programs emerged as key enablers. The findings underscore the need for integrated strategies that combine technological infrastructure with localized capacity-building and financial support. This study contributes empirical insights for policymakers, agritech developers, and development agencies aiming to advance inclusive and sustainable digital transformation in Indonesia’s agricultural landscape.